Interpersonal communication in the diverse workplace get along, get it done, get ahead - Hynes, Geraldine E. (Routledge, 2023)
Foregrounding the vital importance of interpersonal communication and cultural competence in the workplace, this book offers concise, practical strategies for daily communication in a global business environment. The workplace is steadily becoming more diverse, and cultural competence is widely recognized as a key to success, in terms of revenue, profit, market share, and workforce productivity. This and diversity appreciation are the two cornerstones for effective interpersonal communication, facilitating relationship development, improving job satisfaction, commitment, loyalty, and trust, and leading to performance and organizational success. The effectiveness of diversity training sessions and cultural guidebooks can vary-business professionals need a book that presents more than descriptions of culture-bound business practices or prescriptions for valuing diversity. This book is that practical solution, presenting a conceptual model along with tools to put it to work from day one, including cases and examples. With its strategies for reducing diversity miscues, techniques for responding in uncomfortable conversations, and innovative ways to bridge cultural gaps, this book will help current and aspiring leaders across industries build rapport and promote constructive behaviors in a diverse work environment, resulting in organizational success"--